Faktor-Faktor yang Berhubungan dengan Gejala Depresi pada Pasien Insomnia Usia Lanjut di Rawat Jalan - Pratiwi, Amalia Nur; Wahyudi, Edy Rizal; Kusumaningrum, Profitasari; Shatri, Hamzah; Rinaldi, Ikhwan; Gani, Rino Alvani; Wijaya, Ika Prasetya; Susilo, Adityo; Renaldi, Kaka (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. The elderly population is increasing globally, including in Indonesia, where 10.7% of the population in 2020 were elderly. Insomnia is a common health issue among older adults and has been identified as a predictor of depression. This study aims to identify factors associated with depressive symptoms in elderly outpatients with insomnia. Methods. This cross-sectional study was conducted in 2024 on patients aged ≥60 years at the outpatient unit of Cipto Mangunkusumo Hospital (RSCM), Jakarta, Indonesia, using consecutive sampling to select participants. Elderly patients were screened using the Pittsburgh sleep quality index (PSQI), and those with a score >5 (indicating insomnia) were included as study subjects. Data were collected through interviews, covering sociodemographic characteristics, level of loneliness, duration of insomnia, depressive symptoms [Geriatric Depression Scale–15 (GDS-15) items], functional status [Barthel Activities of Daily Living (B-ADL)], cognitive status [Mini-Mental State Examination (MMSE)], nutritional status [Mini Nutritional Assessment (MNA)], and chronic diseases [Cumulative Illness Rating Scale for Geriatrics (CIRSG) score]. Results. The study included 209 elderly subjects with insomnia, with a mean age of 72.88 (SD 6.98) years, and a depression prevalence of 6.7%. Bivariate analysis showed significant associations between dependency (PR 5.24; 95% CI 1.50 – 18.29), malnutrition (PR 11.54; 95% CI 4.77 – 27.92), and chronic disease with a CIRSG score ≥9 (PR 4.15; 95% CI 1.18 – 14.50) and depressive symptoms in elderly patients with insomnia. No significant associations were found between sociodemographic factors, loneliness, duration of insomnia, or cognitive status and depression. Multivariate logistic regression analysis revealed a statistically significant association between malnutrition and depressive symptoms (p < 0.001). Conclusions. There is a significant association between malnutrition and depressive symptoms in elderly outpatients with insomnia. Further cohort studies are recommended to explore the causal relationship between malnutrition and depression in elderly patients with insomnia.